Reduced Emotional Intelligence in Children Aged 9–10 caused by the COVID-19 Pandemic Lockdown - Martín-Requejo, Katya; Santiago-Ramajo, Sandra (John Wiley and Sons Inc, 2022)
It is necessary to know the influence of the current pandemic situation on children's emotional intelligence (EI). Therefore, this study aimed to analyze the difference in 34 Spanish children's EI (aged 9–10) caused by the lockdown. EI was measured with the BarOn Emotional Intelligence Inventory (EQ-i:YV). Results have revealed a reduction in EI, specifically on intrapersonal, interpersonal, and adaptability scales (all p <.01). Thus, the study highlights the negative influence of lockdown situation on children's EI and considering the impact this may have at a cognitive, social, or academic level, it would be convenient to promote its development at school.
Keywords: Emotional Intelligence; psychological support; COVID-19; lockdown; Primary Education; Scopus; JCR